SISTEM INFORMASI AKUNTANSI ANGGARAN LABA DENGAN METODE A POSTERIORI - Sri Wahyuning; Nur Rachmawati; Sumaryanto (Jurnal Akuntansi dan Bisnis, 2022)
Information technology can be used in various human lives, one of which is in the business field. In today's era, it is undeniable that computers with accounting information system equipment are components that must be owned by companies to help ease the task of company performance. One of them is BKM which is specifically aimed at poverty alleviation and community development. UPK itself is a non-profit organization or an organization whose main objective is to support an issue or matter in attracting public attention for a non-commercial purpose, without any attention to things that are for-profit. The allocation has also been divided according to their respective portions. This study aims to simplify the presentation of profit budgeting at BKM which is still not structured and does not provide clarity about the results of the funds that should be used as the allocation of community activities. Profit budgeting is also not carried out periodically and is still manual in recording so that profits cannot be known in detail. In overcoming the problems above, by using a programmed system with the a posteriori method, the institution can easily record every operational budget to the profit budget so that it can allocate funds for community activities in a structured manner